Putative dendritic correlates of chronic traumatic encephalopathy: A preliminary quantitative Golgi exploration. Issue 7 (23rd September 2020) - Warling, Allysa; Uchida, Riri; Shin, Hyunsoo; Dodelson, Coby; Garcia, Madeleine E.; Shea‐Shumsky, N. Beckett; Svirsky, Sarah; Pothast, Morgan; Kelley, Hunter; Schumann, Cynthia M.; Brzezinski, Christine; Bauman, Melissa D.; et al.
Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disorder that is associated with repetitive head impacts. Neuropathologically, it is defined by the presence of perivascular hyperphosphorylated tau aggregates in cortical tissue (McKee et al., 2016, Acta Neuropathologica, 131, 75–86). Although many pathological and assumed clinical correlates of CTE have been well characterized, its effects on cortical dendritic arbors are still unknown. Here, we quantified dendrites and dendritic spines of supragranular pyramidal neurons in tissue from human frontal and occipital lobes, in 11 cases with ( M age = 79 ± 7 years) and 5 cases without ( M age = 76 ± 11 years) CTE. Tissue was stained with a modified rapid Golgi technique. Dendritic systems of 20 neurons per region in each brain ( N = 640 neurons) were quantified using computer‐assisted morphometry. One key finding was that CTE neurons exhibited increased variability and distributional changes across six of the eight dendritic system measures, presumably due to ongoing degeneration and compensatory reorganization of dendritic systems. However, despite heightened variation among CTE neurons, CTE cases exhibited lower mean values than Control cases in seven of the eight dendritic system measures. These dendritic alterations may represent a new pathological marker of CTE, and further examination of dendritic changes could contribute to both mechanistic and functional understandings of the disease. Abstract : Macroscopic gray matter changes have been well documented in chronic traumatic encephalopathy (CTE). The present study examined microscopic gray matter changes in CTE by comparing the dendritic arbors of supragranular pyramidal neurons from prefrontal and occipital cortices in both Control and CTE cases. CTE neurons exhibited significantly lower mean dendritic measure values than did Control neurons, while also displaying considerably greater variability across measures. These changes may be a newly described pathological marker of CTE and could supplement current mechanistic and functional understandings of the disease.